KARAKTERISASI KOMPOSIT RESIN EPOKSI SERBUK KAYU - Darsa, Darwin Sugan; Rizki, Muhammad (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Has been done sinthesize composite from saw dust with epoxy resin where as ratio of saw dust mass is 1 gram : 2 grams : 3 grams and same amount of epoxy resin 7.086 grams. Mass addition of saw dust yield darker composite appearance on the biggest one, and based on mass and volume measurement of composite yield lower density of composite by the density of each samples are 1.26 g/cm3, 1.15 g/cm3, dan 1.12 g/cm3. Then based on XRD characterisation result identification of two fase epoxy resin and saw dust yields the increasing of samples’ crystallinity as the increasing of saw dust sequently 20.58%,24.99 %, dan 25.57%. Keywords: Composite, Epoxy Resin, Saw Dust, Mass Addition.